The Role of the Use of Social Media Marketing in Achieve Business Sustainability - SHIRATINA, Aldina; RACHBINI M, Didik J; AFFINI, Dinar nur (Indonesia Strategic Sustainability, 2024)
Based on the results of a survey conducted by the Central Statistics Agency in 2019, from the 3,504 block census, 15.08% of perpetrators undertook activity through the Internet. Using the online method, most of the data from this sale from 2017 until 2018 was 45.31%. Perpetrators undertaking sales via the Internet in 2018 as much as 72.83 %. Meanwhile, the perpetrator's new venture made sales via the Internet in 2019 by as much as 25.11 %. Temporarily, frequent payments carried out in the sales process via the Internet are paid on the spot or COD (cash on delivery), i.e., as much as 83.73%. Several perpetrator businesses use method delivery directly by the party seller, which is as much as 55.96%. Competition increases effort and strictness, so business people must implement effective strategies to avoid losing to competitors. There is a technique of marketing that can give Lots of benefits to development companies, and that is digital marketing. Micro is starting to use social media to promote the product actively, so it is necessary to apply digital marketing, mainly via social media. Micro-business actors who become subject to research determine social media platforms. Based on the Analysis Situation moment, Devotion To this Community is done as a role strategy use of Social Media Marketing in.